Phase 1 study of sorafenib and irinotecan in pediatric patients with relapsed or refractory solid tumors. Issue 11 (12th August 2021) - Meany, Holly J.; Widemann, Brigitte C.; Hinds, Pamela S.; Bagatell, Rochelle; Shusterman, Suzanne; Stern, Emily; Jayaprakash, Nalini; Peer, Cody J.; Figg, William D.; Hall, O. Morgan; Sissung, Tristan M.; Kim, Aerang; et al.
Abstract: Background: Sorafenib, an orally bioavailable, multitarget tyrosine kinase inhibitor, and irinotecan, a topoisomerase I inhibitor, have demonstrated activity in pediatric and adult malignancies. We evaluated the toxicity, pharmacokinetic (PK), and pharmacogenomic (PGX) profile of sorafenib with irinotecan in children with relapsed or refractory solid tumors and assessed the feasibility of incorporating patient‐reported outcome (PRO) measures as an adjunct to traditional endpoints. Methods: Sorafenib, continuous oral twice daily dosing, was administered with irinotecan, orally, once daily days 1‐5, repeated every 21 days (NCT01518413). Based on tolerability, escalation of sorafenib followed by escalation of irinotecan was planned. Three patients were initially enrolled at each dose level. Sorafenib and irinotecan PK analyses were performed during cycle 1. PRO measurements were collected during cycles 1 and 2. Results: Fifteen patients were evaluable. Two of three patients at dose level 2 experienced dose‐limiting toxicity (DLT), grade 3 diarrhea, and grade 3 hyponatremia. Therefore, dose level 1 was expanded to 12 patients and two patients had DLT, grade 4 thrombocytopenia, grade 3 elevated lipase. Nine of 15 (60%) patients had a best response of stable disease with four patients receiving ≥6 cycles. Conclusions: The recommended dose for pediatric patients was sorafenib 150 mg/m 2 /dose twice daily with irinotecan 70 mg/m 2 /dose daily × 5 days every 21 days. This oral outpatient regimen was well tolerated and resulted in prolonged disease stabilization. There were no significant alterations in the PK profile of either agent when administered in combination. Patients were willing and able to report their subjective experiences with this regimen.